2015
DOI: 10.1103/physrevlett.114.233601
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Generation of Nonclassical Light on Chip via Detuned Photon Blockade

Abstract: The on-chip generation of nonclassical states of light is a key requirement for future optical quantum hardware. In solid-state cavity quantum electrodynamics, such nonclassical light can be generated from self-assembled quantum dots strongly coupled to photonic crystal cavities. Their anharmonic strong lightmatter interaction results in large optical nonlinearities at the single photon level, where the admission of a single photon into the cavity may enhance (photon tunneling) or diminish (photon blockade) th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
131
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 37 publications
7
131
0
1
Order By: Relevance
“…2b), and its quality improves for higher detuned emitter-like peaks. This is consistent with the findings in single-emitter CQED systems where the photon blockade at the polariton peak frequency strengthens with the emitter-cavity detuning [3]. We identify a novel effect of reduced second order coherence value at the frequency of the subradiant peakthe subradiant photon blockade (yellow arrows in Fig.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…2b), and its quality improves for higher detuned emitter-like peaks. This is consistent with the findings in single-emitter CQED systems where the photon blockade at the polariton peak frequency strengthens with the emitter-cavity detuning [3]. We identify a novel effect of reduced second order coherence value at the frequency of the subradiant peakthe subradiant photon blockade (yellow arrows in Fig.…”
supporting
confidence: 80%
“…The photon blockade (PB) effect prevents the absorption of the second photon at specific frequencies due to the nonlinearity of the emitter that dresses the energy states and leads to an anharmonic ladder. This effect has been extensively studied in single-emitter (N = 1) atomic [1, 2] and quantum dot [3,4] cavity quantum electrodynamics (CQED), as well as in circuit QED systems [5]. Here, the effect occurs at the frequencies of the dressed states so-called polaritons (polaritonic PB) and results in a faster emission rate of single photons compared to the bare emitter.…”
mentioning
confidence: 99%
“…In the strong coupling regime, where the coupling between the two-level system and the cavity is larger than the cavity decay rate ðg > κÞ [4], photon blockade has been demonstrated in atomic systems [5], quantum dots in photonic crystal cavities [6], and circuit QED [7,8]. At the onset of the weak coupling regime (g ≈ κ), it has been shown that by detuning the dipole transition frequency with respect to the cavity resonance, photon blockade can still be observed [9]. However, moving further into the weak coupling regime (g < κ), which is much easier to achieve [10,11] (in particular if one aims for a small polarization mode splitting), the conventional photon blockade is no longer possible because the energy gap between the polariton states vanishes.…”
mentioning
confidence: 99%
“…The photon blockade has been theoretically and experimentally researched in a variety of systems, such as cavity quantum electrodynamics [1][2][3][4][5][6][7][8][9]. However, experimental realization of strong photon blockade is still a challenging pursuit, because the observation of strong photon blockade requires large nonlinearities with respect to the decay rate of the system.…”
Section: Introductionmentioning
confidence: 99%